1996
DOI: 10.1037/0894-4105.10.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spaced repetitions on amnesia patients' recall and recognition performance.

Abstract: This study examined the effects of repetition and spacing of repetitions on amnesia patients' recognition and recall of a list of words. Like controls, amnesia patients recognized items better when repetitions were spaced compared with when they were massed. This finding was attributed to the additional rehearsal that distributed presentations typically encourage. Amnesia patients also showed normal spacing effects in a recall task, suggesting that they were able to benefit from the variable encoding that spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
7
29
0
Order By: Relevance
“…Like individuals with intact memory, patients with selective amnesia show improved recognition memory following spaced repetition (Cermak, Verfaellie, Lanzoni, Mather, & Chase, 1996; Hillary et al, 2003; Verfaellie, Rajaram, Fossum, & Williams, 2008), and similar findings have been obtained in patients with severe memory impairments in the context of traumatic brain injury (Hillary et al, 2003) and Alzheimer’s disease (Moulin, Perfect, & Jones, 2000). However, in a study by Cermak et al (1996), amnesic patients performed no better following massed repetition than following a single presentation on an immediate recall or recognition test – a finding that contrasts with the pattern seen in control subjects.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Like individuals with intact memory, patients with selective amnesia show improved recognition memory following spaced repetition (Cermak, Verfaellie, Lanzoni, Mather, & Chase, 1996; Hillary et al, 2003; Verfaellie, Rajaram, Fossum, & Williams, 2008), and similar findings have been obtained in patients with severe memory impairments in the context of traumatic brain injury (Hillary et al, 2003) and Alzheimer’s disease (Moulin, Perfect, & Jones, 2000). However, in a study by Cermak et al (1996), amnesic patients performed no better following massed repetition than following a single presentation on an immediate recall or recognition test – a finding that contrasts with the pattern seen in control subjects.…”
supporting
confidence: 57%
“…However, in a study by Cermak et al (1996), amnesic patients performed no better following massed repetition than following a single presentation on an immediate recall or recognition test – a finding that contrasts with the pattern seen in control subjects. This finding is surprising in light of the documented benefit associated with a single, long study presentation in patients with severe memory impairment.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Most striking in the anterograde memory domain, unlike control participants, H.C.'s recognition memory performance does not appear to benefit from semantic encoding of verbal study material, a feature that has been noted in individuals with Korsakoff syndrome in whom mammillary bodies are reduced (Cermak et al, 1974). Her memory retrieval nevertheless benefits from repetition when repeated items in a study list are spaced rather than presented in immediate succession (Green et al, 2014), an effect that has also been demonstrated in Korsakoff patients (Cermak et al, 1996). Areas of cognitive function that had not undergone rigorous investigation in developmental amnesia until H.C. include memory for public events, which was found to be impaired (Rosenbaum et al, 2011;see Maguire et al (2001) for initial findings of intact public event memory in Jon), and the ability to hold information online in working memory, which was intact for famous faces and known vocabulary but impaired when the information was previously novel (Rose et al, 2012;see Allen et al (2014) and Baddeley et al (2011) for complementary evidence in Jon).…”
Section: Introductionmentioning
confidence: 68%
“…These studies encompass a wide variety of fields including Neuropsychology [25] Occupational Therapy [26], Data Management [27], HCI [28], Psychology [29] [30] and Experimental Child Psychology [31] all of which point to positive effects when utilising SRS to augment existing practices. Perhaps most relevant to the field of SLT is posited in [31], where the author concludes that "results are consistent with the hypothesis that spaced repetition effects in recognition are produced by fundamental memory mechanisms that are operational at a very early age and which undergo little change in development".…”
Section: Related Workmentioning
confidence: 99%